Economic Statecraft of Small States in Response to Great Power Strategic Rivalry-Take Malaysia as An Example - Zhao, Xinlei (Business and Economic Research, 2024)
The foreign economic statecraft of state actors in International Relations (IRs) have often attracted much attention and discussion among scholars, but most of the existing research focuses on the economic statecraft choices of great or medium-sized powers, and there is a lack of discussion on the economic statecraft of small state actors. From the perspective of International Political Economy (IPE), this paper takes Neoclassical Realism (NCR) as the theoretical basis and adopts case studies and process tracing to analyze how Malaysia has responded to the competition of great powers such as the United States, China and Japan with different economic statecrafts. The results show that small states, like great power, possess the ability to implement different economic statecrafts, and the ability threshold, initiative, and rationality of goals are the conditions that shadow whether small countries can implement economic statecrafts. State favorability at the system level and interest preferences at the unit level jointly shape the three modes of economic statecrafts that small states use to cope with great power competition, including: offensive economic statecraft, defensive economic statecraft, and composite economic statecraft. Depending on their relative relationship and status with great powers, small states flexibly apply different economic statecrafts to realize the goals of foreign economic development and maintain national security.